The use of a special nutritional training program to improve the muscular activity of the muscles of the lower extremities and the achievement in the long jump - Hussein, Ghassan Bahri Shamkhi; Alwan, Muhammad Fadhil; Abaas, Imran Ali (International Journal of Psychosocial Rehabilitation, 2020)
Long jump competitions are interesting competitions for the player and spectator, and the long jump competition requires a great deal of muscular strength associated with speed (strength distinguished by speed) and also requires the player to have complete control over performance and physical ability and to possess some special physical attributes. The importance of the research lies in the interest in athletics activities, including the long jump. Therefore, scientific methods of measurement and training must be adopted. The research problem crystallized in the presence of weakness in the muscular strength of the lower extremities and the level of achievement of the research sample, according to the opinion of the researchers. The study aimed to identify the level of electrical activity of the muscles of the lower extremities and the level of achievement for the research sample under study. The researchers assumed that there were statistically significant differences between the pre and posttests in the values of the electrical activity of the target muscles and the level of achievement in favor of the post test for the research sample under study. The researchers used the experimental method on 5 of the long jump effectiveness players, and after analyzing and treating the values of the studied functional indicators for the research sample, the researchers reached several conclusions, including that the training and nutritional program had a clear effect on improving the work of the muscles targeted in the study through the results in the post test.